Metabolomics Based on MS in Mice with Diet-Induced Obesity and Type 2 Diabetes Mellitus: the Effect of Vildagliptin, Metformin, and Their Combination - Tomášová, Petra; Bugáňová, Martina; Pelantová, Helena; Holubová, Martina; Šedivá, Blanka; Železná, Blanka; Haluzík, Martin; Maletínská, Lenka; Kuneš, Jaroslav; Kuzma, Marek (Applied biochemistry and biotechnology, 2019)
Type 2 diabetes mellitus (T2DM) is a major epidemiological problem. Metformin and vildagliptin are well-established antidiabetic drugs. The aim of the study was to evaluate the changes of plasma metabolic profile induced by a high-fat diet (HFD) and subsequent oral administration of metformin, vildagliptin, and their combination in a mouse model of diet-induced obesity (DIO)/T2DM analyzed using quadrupole-time-of-flight mass spectrometry (qTOF-MS). Metformin treatment increased the levels of butyrylcarnitine and acylcarnitine C18:1 concentrations and decreased the levels of isoleucine concentrations compared to untreated HFD mice. Vildagliptin treatment increased levels of butyrylcarnitine and acetylcarnitine. In summary, our metabolomics study revealed multiple differences between obese diabetic HFD mice and lean standard chow diet (SCD) mice, which were partially modifiable by subsequent metformin and vildagliptin treatment.
Keywords: obezita; Mass Spectrometry; Mass spectrometry; metformin; Metabolomics; Diet-induced obese mice; Metformin; metabolomika; zvířata; myši; myši inbrední C57BL; reprodukovatelnost výsledků; Mice; Diabetes Mellitus, Type 2; Hypoglycemic Agents; Male; Reproducibility of Results; Plasma; Mice, Inbred C57BL; hypoglykemika; Obesity; Animals; vildagliptin; mužské pohlaví; kombinovaná farmakoterapie; diabetes mellitus 2. typu; hmotnostní spektrometrie; Disease Models, Animal; Vildagliptin; Drug Therapy, Combination; modely nemocí na zvířatech